Fase yang Terabaikan: Disfungsi Komunikasi Keluarga Otoriter dan Konstruksi Ideasi Parasida pada Remaja - Elisa Zakira; Wilodati Wilodati; Mirna Nur Alia Abdullah (Universitas Al Azhar Indonesia, 2026)
The phenomenon of children killing their parents, commonly referred to as parricide, has been increasingly documented in Indonesia since 2016. While most previous studies have examined parricide retrospectively after the crime has occurred, this study focuses on the pre-criminal stage by mapping the literature to understand how family communication patterns within authoritarian parenting may contribute to the emergence of parricidal ideation. A scoping review approach was employed using a four-stage methodological framework strengthened by the JBI guidelines, resulting in the analysis of 28 relevant articles. The review identified four key findings. First, authoritarian parenting consistently fosters a protective communication pattern characterized by enforced obedience, suppression of children’s voices, and limited opportunities to question parental authority. Second, adolescents may develop negative self-perceptions through symbolic identities formed in the family environment, where repeated demeaning communication erodes self-concept and may become a psychological threat. Third, accumulated emotional pressure can develop into ideation of extreme violence, including thoughts of killing one’s parents. Fourth, densely populated residential environments may exacerbate family dysfunction by reinforcing parental authority and limiting adolescents’ opportunities to escape ongoing conflicts, thereby worsening their psychological well-being. These findings provide important insights for the development of child protection policies and family communication intervention programs, particularly in densely populated communities in Indonesia.Keywords - Authoritarian Parenting, Densely Area, Parricide Ideation, Protective Family Communication.